Supply Chain Management Model on Start-Up Business - Nainggolan, Romauli (Jurnal Entrepreneur dan Entrepreneurship, 2019)
Supply chain management is an important part in achieving the efficiency of the company. The supply chain for early-stage businesses is further compared to large and advanced businesses. This research offers a management model for the supply chain of non-F & B start-up businesses established by Universitas Ciputra students and discuss the strategy for planning raw materials from suppliers. The consideration of choosing the non-Food & Beverage businesses was merely because the products have longer physical endurance so they can be stored in warehouses for preparation, so it is assumed to have longer supply chain. The research respondents were 30 non-Food and Beverage start-up businesses operating more than two years. From the results of the study there were two findings. First, there are three kinds of supply chain management models adopted by the student's start-up business. Model 1 consist of Suppliers - Manufacturers - Distributors - Resellers - Consumers. Model 2 consist of Suppliers - Manufacturers - Resellers - Consumers. Model 3 consist of Suppliers - Retailers - Consumers. Second, in order to provide raw materials, 40% non-F & B student's start-up businesses using a small supplier strategy with two suppliers. 7% start businesses using many supplier strategies with four suppliers. Non-Food & Beverage businesses have longer physical endurance so they can be stored in warehouses for inventory